THE IMPACT OF THE UNPAYABLE ACCOUNTS RECEIVABLE ON THE LIQUIDITY LEVEL AT PT ABC - Syarief Gerald Prasetya (The Accounting Journal of Binaniaga, 2017)
The capability of a company to settle down its short-term liabilities hasbeen one factor to determine whether the financial of a company is good or not. This kind of capability is the liquidity level. One factor that has determined the company’s liquidity level whether it is huge or small one is depending on the total of the accounts receivable owned by the company. The method of this research has applied the associative descriptive method describing the connection of two or more variables.To identify the liquidity level of the company, it has been applying a proxy analysis of liquidity ratio. Identifying the impact of the unpayable accounts receivable on the liquidity level has been applying a simple regression equation. The test result using t-test has indicated a significant effect. Moreover, it has been noticed that the amountof unpayable account receivables has been determining the liquidity level of the company. The suggestion to increase the liquidity level is by reducing the total amount of current liabilities.Keywords: bad debt, liquidity, account receivable